Marketing orientation of the dairy farmers in co-operative farming system* - Ghosh, R K; Goswami, A; Mazumdar, A K; Islam, S (The Indian Journal of Animal Sciences, 2011)
The present study was carried out at purposively selected Gaighata and Bagdah block ofNorth-24 Pgs district, West Bengal. From each of the purposively selected 2 blocks, 25% (approximately) of the village level milk co-operative societies (VLMCSs) were selected randomly. In this way 10 VLMCSs (25%) from Gaighata block and 20 (25.64%) from Bagdah Block were selected randomly. From each of the selected VLMCS four dairy farmers were selected randomly out of which both member ofco-operative society (MCS) and non-member of co-operative society (NMCS) were 2 in number. Thus 60 MCS and 60 NMCS (total 120 respondents) were selected, which constituted the sample of the present study. The study revealed that all the socio-psychological and communication variables were having significa t relationship with the marketing orientation of the dairy farmers in both MCS and NMCS. Results of path analySIS showed that communication source was the key variables that influence the marketing orientation ofthe dairy farmers both in MCS and NMCS. Â